Insight of the size dependent bioavailability and health risk assessment of arsenic in resuspended fly ash from power plants. (1st November 2022) - Shen, Yi-Wen; Zhao, Hao; Xie, Jiao-Jiao; He, Kai-Qiang; Pang, Jia-Feng; Guo, Qi; Duan, Xue-Lei; Yuan, Chun-Gang; Zhang, Ke-Gang; Zhu, Hong-Tao; Li, Bao-Hui
Highlights: Fly ash samples were classified with different sizes by a self-made resuspension device. The bioavailability of arsenic in fly ash increased with the decrease of particle size. The ingestion and inhalation bioavailability of arsenic relied on non-specifically sorbed and specifically-sorbed fractions. ∑CR values of the samples from the power plants exceeded acceptable threshold or even tolerable risk level. Abstract: Arsenic can obviously be accumulated in fly ash, and can pose serious health exposure to the on-site workers during the process of reuse and treatment via resuspension due to the fine particle size. However, the knowledge about that is very limit for the lack of effective resuspension equipment. In this study, a self-made resuspension device was designed and applied to re-collect fly ash with different sizes (TSP, PM10 and PM2.5 ). A sequential extraction procedure and in vitro tests (simulated lung fluid and simulated gastrointestinal fluid) were employed to explore the fractions and bioavailability of arsenic in the resuspended fly ash. Arsenic contents in fly ash increased with the decrease of particle size ranging from 15.15 to 67.78 mg kg −1 . Five fractions were identified, and their distribution patterns in the particles with different sizes were also characterized. The fraction distribution of arsenic in fly ash was affected by particle size, and the ingestion and inhalation bioavailability of arsenic mainly depended on non-specifically sorbed and specifically-sorbed fractions. The bioavailability factors (BFs) of arsenic increased with the decrease of particle size, exceeding or approaching the high-risk level (BFs > 0.55). Regarding non-carcinogenic health risk via ingestion and inhalation, the HQ (Hazard Quotient) values of arsenic were lower than the safe level (HQ < 1). Notably, ingestion was the dominant contributor to cancer risk with CR values above acceptable threshold and under tolerable risk level (except three plants). The classification of fly ash is conducive to evaluate the health risk of arsenic more accurately in resuspended fly ash.